FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN ASLI DAERAH (PAD) PROVINSI JAWA BARAT - Aninda Rizkyana (2022)
Regional Original Revenue is one of the important sources of revenue for the region and economic growth, because it determines the level of financial independence of the regency/city government can be seen based on the ratio of regional original income to the regional revenue and expenditure budget (APBD). One of the factors driving the increase in regional original income is the independence of a region by optimally utilizing the potential of the region so that the taxes and levies obtained are also greater. This study is a quantitative study that aims to determine the effect of Hotel Tax, Entertainment Tax, Regional Retribution and Total Population on Regional Original Income. This study uses data from 6 regions in West Java Province, namely Bandung City, Bekasi City, Depok City, Bogor City, Bogor Regency and Bandung Regency with the period from 2011 to 2020. The method used in this study is Fixed Effect panel data regression analysis with Least Square Dummy Variable (LSDV) method. The results of this study indicate that (1) hotel tax has an effect on local revenue (2) entertainment tax has no effect on regional original income (3) regional retribution has an effect on regional original income (4) population has no effect on regional original income.